THE STUDY OF EARLY DIAGNOSIS OF PERSONALITY DISORDER WITH EXPERT SYSTEM BUILDER - Cynthia Hayat (STMIK JAKARTA STI&K, 2019)
Personality disorders are chronic psychological disorders that can affect work, family and social life of a person. In some cases, the possibility of people do not realize that they have a personality disorder as a way of thinking and behaving seems natural to the patient, and the patient may blame others. To diagnose a personality disorder early, then made an application using expert system builder tools. Data collected through interviews with an expert who understands the problem of personality disorders. By utilizing the concept of expert system on expert system builder tool (ESB) there was a transfer of knowledge from experts to the application to be made. This application is made to follow the rules knowledge base, decision tree and decision table. Stages of the design is to design a search rule identification of diabetes mellitus, then design decision table based on the rule-based and subsequently designed a decision tree based decision table that has been created. Keywords : Personality disorders diagnosis, Expert system, Expert system builder